Factors Influencing Consumers' Purci-Iase Intention For Milk Powder In Penang - Yow, Bee Charn (2014)
This study demonstrate the adapt ion of Theory of Planned Behavior (TPB) to examine how product knowledge, product involvement, perceived benefit, perceived risk and country of origin image influence consumers' purchase intention for milk powder and how consumers' attitude mediates these variables on consumers' purchase intention. A self-administered questionnaire was developed using established scales. A survey on 200 respondents was conducted in Penang, Malaysia through online survey questionnaire. Statistical Package for the Social Science (SPSS) was used to analyze the data. The study findings revealed that product knowledge, product involvement and perceived benefit were positively and significantly related to purchase intention. Perceived risk had negative but no significant relationship with purchase intention. Country of origin image had no significant effect on purchase intention. In addition, product knowledge, product involvement and perceived benefit had positive and significant relationship with consumers' attitude. Perceived risk was negatively and significantly affected consumers' attitude. Country of origin image was found no significant relationship with consumers' attitude. Attitude which is the mediating variable in this study was found to have a mediation effect in the relationship between product knowledge, product involvement, perceived benefit, perceived risk, country of origin image and purchase intention for milk powder. The findings were limited to include only consumers in Penang which cannot be generalized across the whole Malaysia. It is recommended to include other states in Malaysia for future study. This study provides an in-depth understanding of Malaysia consumers' purchase intention towards milk powder.